PENERAPAN METODEBERMAIN ANAK USIA DINI PADA KELOMPOK B UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG PERMULAAN DI TK AL-FALAH - Rina Septiadiningsih; Euis Rohaety; Lenny Nuraeni (IKIP Siliwangi, 2019)
Sensitive period is the right time to instill the basis of the importance of counting. In addition to counting skills that must be developed also pay attention to the application of learning used. However, in the learning process, teachers often forget the importance of playing methods. If too often with giving assignments the child will feel bored, therefore what is used is the method of playing. Play method is one method that can be used by teachers to teach the ability to count children in the beginning. Based on this background, the purpose of this study was to determine the effect of the use of playing methods on initial numeracy skills. This study used the Quasi Experiment method with the Nonequevalent Control Group Design research design. The results of the pre test showed that there were no significant differences in the experimental group and the control group with p-value> 0.05, which was 0.135> 0.05 which was tested by the two average test results. While the post-test results showed that the initial numeracy ability after the application of the playing method experienced a significant difference with the p-value <0.05, that is with the results of 0.0001 with the Mann-Whitney test. This method of playing can be used as a learning suggestion for educators to improve their ability to have an early start.